OPTIMALISASI TINGKAT PEMBIAYAAN MUDHARABAH DI PERBANKAN SYARIAH STUDI KASUS: PT. BRI SYARIAH PEKANBARU - AHMAD HAMDALAH (An-Nida', 2017)
Sharia bank is identified with the term profit sharing bank, it is reflected from one type of financing in the form of profit sharing or mudharabah financing. However, the condition in the field that portion of mudharabah financing is still too small compared with other types of non-profit financing. Therefore, this study aims to explore the system of mudharabah financing in PT. BRISyariah Pekanbaru, identified the constraints faced and the efforts made in improving mudharabah financing as well as and analysis of that financing. This research is Field Research and is analytical descriptive that is describe and analyze findings that it can. Obtained from the finding that the operational Mudharabah Financing in BRI Syariah is 100% including Mudharabah Linkage category, while the obstacles faced include complex mudharabah agreement, insufficient Human Resources (SDI), Information Technology (IT) system that has not supported and customer responsibility. Mudharabah financing optimization efforts are done in the form of financing with Linkage Program model, financing to special customers, and improving SDI.